POWER RELATIONS REPRESENTED IN BURNT SHADOWS AND HOPE AND OTHER DANGEROUS PURSUITS - Muhamad Arifin Ilham (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This paper examines the critics of power in Burnt Shadows and Hope and Other Dangerous Pursuits. As a literary study, this paper tries to find the main cause of the political and economic downfall of colonized countries and countries destined for immigrants and diasporas mentioned in the text by focusing on political clashes between policy makers and the people through power relations, a theory suggested by Michel Foucault to deconstruct interlinked power distribution among social hierarchies. These novels talk about the dynamic life of a post-war family and immigrants, victims of the policy makers who hold the power over the people. The ignorance over millions of human lives turns them into mere statistics rather than sentient beings. Therefore, this paper argues that these novels try to evoke humanity’s issues by intertwining storytelling for every chapter through characters’ intrigues of life related to the actual real-world problem. This paper uses a descriptive qualitative method, analyzing textual evidence written in the narratives. The findings indicate that the characters express their resistance through personal traits, pop-culture references, and acts of defiance against those in power, despite feeling powerless.